Genetic characterization, age and reproductive status of dwarf sperm whales (Kogia sima) stranded along the Italian coastlines - MAIO, NICOLA; FIORAVANTI, TATIANA; LATINI, LUCREZIA; PETRACCIOLI, AGNESE; MEZZASALMA, MARCELLO; INSACCO, GIANNI; SPLENDIANI, ANDREA; POLLARO, FRANCESCO; GUARINO, FABIO MARIA; CAPUTO BARUCCHI, VINCENZO (Mediterranean Marine Science, 2024)
The knowledge of the life history traits of cetaceans, especially in the case of species that are difficult to observe in the wild, often benefits from the study of stranded individuals. The dwarf sperm whale (Kogia sima) is a vagrant cetacean species in the Mediterranean Sea, which is rarely sighted in water and occasionally is found stranded along the Italian coasts. In this work, we investigated the genetics, age, and reproductive status of three dead individuals (1 male, 1 female, 1 unsexed), stranded in three different sites along Italian coastlines. We used mitochondrial DNA markers for tracing the geographical origin of the animals, tooth sectioning as a proxy for their age estimation and gonadal histology for evaluating their reproductive status. Genetic analyses revealed that the male and the female are K. sima belonging to the Atlantic clade (A clade). The female, with a total body length (TBL) of 1.95 m, had an estimated age of 12 years, and ovaries with one corpus luteum. The male, with a TBL of 2.07 m, had testicles in late spermatogenesis and an estimated age of 22-24 years. From the unsexed individual, which had an estimated age of at least 20 years, no gonadal samples were obtained as it was stranded as a skeleton. Our findings will contribute to increase the knowledge of some unexplored provenance and life-history traits of K. sima visiting the Mediterranean.